Ecological security measurement based on functionality-organization-stability in inland of Three Gorges Reservoir area - Zhan, Likun; Guo, Xianhua; Li, Tingzhen; Liu, Xi; Lu, Chendong; Zhang, Na; Lu, Zenghui (Journal of Environmental Engineering and Landscape Management, 2022)
The spatial-temporal heterogeneity of landscape ecological security has been carried out for the Zhong County in this work based on the framework of “functionality-organization-stability” using the multidate Landsat TM image of 2000, 2006, 2012 and 2018 as the basic data. During the research period, landscape ecological security situation in Zhong County indicates a trend of deteriorating. The high ecological security zone was constantly shifting to the low ecological security zone from 2000 to 2018. The ratios were 13.40%, 61.32%, 28.34%, and 13.33%. The low ecological security area in research area focuses on the northeast part and middle part, while the high-security area focuses on Yangtze river way and its both sides and Northwest. The main obstacle factor of landscape ecological security transfers into stability from functionality. Therefore it suggests to optimize land use pattern in landscape planning and construction in the future in order to raise the landscape ecological security level.